Educational prerequisites to ensure the use of students’ reflection practice in the learning process - Jurs, Pavels; Spehte, Elita; Samusevica, Alida; Kulberga, Inta (Nurture, 2023)
Purpose: The objective of this study is to analyse the relationship between teachers and the pedagogical requirements of the learning process that ensure that students use reflective practice in the learning process by studying the theoretical framework of the concept of reflection. Design/Methodology/Approach: A phenomenological research design was chosen which is based on the paradigm of humanistic research. The method of inductive content analysis was chosen for the analysis of qualitative data. Findings: The empirical findings of the research indicate that setting goals is essential for the reflection process. Students must actively participate in the process by focussing on, evaluating and applying critical thinking to specific content in order to achieve those goals. Conclusion: The study highlights the importance of reflection activities in the learning process which allow students to base their decisions on their previous experiences, choose and verify the correctness of learning concepts, focus on growth, improve research skills and create new experiences. Teachers need to incorporate this into practice by actively involving students in the learning process to facilitate the reflection process. Practical Implication: The result indicates that reflection practice is crucial in the learning process. Teachers need to incorporate this into a practice that allows the students to be actively involved in the learning process and take responsibility for their progress.